Using Service-oriented architectures towards Rights Management Interoperability - Serrão, C.; Dias, J.; Delgado, J. (Proceedings of the Second International Joint Conferences on Computer, Information and System Sciences, and Engineering (CISSE2006), Bridgeport, USA, 2006)
In a World where all forms of digital content are growing at an increasing rate, there are some issues that need to be addressed. Intellectual Property Rights (IPR) is one of the most crucial and important ones. If in the analogue World the IPR issues are addressed in a fairly well manner, the same doesn’t apply to the digital one. Users are permanently confronted with this important dilemma – to be or not to be a pirate. The choice is not obvious or trivial because it implies choosing between something which freely available on a P2P network or opting to pay an amount of money to get the same content that is protected and won’t work everywhere. In this paper, we will provide some information about the problems arising from the fact that protected content has obtrusive limitations, and we will present part of a solution that can be used to address the DRM interoperability problems based on Service-oriented architectures.